Morphological and biological properties of bartonellae - Nauck, Ernst G. (1957)
At the Institute for Tropical Diseases in Hamburg, founded by Bernhard Nocht in 1900, have made significant contributions to the study of the etiological agent of Carrion's disease. Organisms belonging to the group of bartonellae were studied by a number of researchers at different times, with different methods and from different viewpoints. The Institute for Tropical Diseases in Hamburg must feel so intimately connected with investigating and certifying bartonellae pleased that through the work of the contributors to the older generation as well as in more recent times, been able to provide some important studies knowledge of this interesting group of etiologic agents.